Nobody's perfect a story for children about perfectionism - Burns, Ellen Flanagan; Villnave, Erica Pelton (Washington, D.C. Magination Press, 2009)
Sally overcomes her perfectionism when her teachers and mother help her realize that making mistakes is a part of learning, and that doing her best is good enough.
"Ages 8-12/grades 3-6."--Cover p. [4].
Keywords: Perfectionism (Personality trait) -- Fiction